2019
DOI: 10.3390/ijms20194946
|View full text |Cite
|
Sign up to set email alerts
|

Transgelin, a p53 and PTEN-Upregulated Gene, Inhibits the Cell Proliferation and Invasion of Human Bladder Carcinoma Cells In Vitro and In Vivo

Abstract: Transgelin (TAGLN/SM22-α) is a regulator of the actin cytoskeleton, affecting the survival, migration, and apoptosis of various cancer cells divergently; however, the roles of TAGLN in bladder carcinoma cells remain inconclusive. We compared expressions of TAGLN in human bladder carcinoma cells to the normal human bladder tissues to determine the potential biological functions and regulatory mechanisms of TAGLN in bladder carcinoma cells. Results of RT-qPCR and immunoblot assays indicated that TAGLN expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
(81 reference statements)
2
23
1
Order By: Relevance
“…The 5 -deletion report assays demonstrated that p53-induced maspin expression in bladder carcinoma cells was dependent on the 5 -flanking region fragment (−567 to −162) of the human maspin gene (Figure 7). Our study is consistent with a previous report that identified two p53 binding sites (GGCATGTTGGAGGCCTTTG and GGACAAGCTGCCAAGAGGCTTGAGT) in the promoter of the human maspin gene [40]. However, our study indicated that p53 may affect the reporter activity of the reporter vector containing the DNA fragment (−567 to −363), which does not have a putative p53 binding site.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The 5 -deletion report assays demonstrated that p53-induced maspin expression in bladder carcinoma cells was dependent on the 5 -flanking region fragment (−567 to −162) of the human maspin gene (Figure 7). Our study is consistent with a previous report that identified two p53 binding sites (GGCATGTTGGAGGCCTTTG and GGACAAGCTGCCAAGAGGCTTGAGT) in the promoter of the human maspin gene [40]. However, our study indicated that p53 may affect the reporter activity of the reporter vector containing the DNA fragment (−567 to −363), which does not have a putative p53 binding site.…”
Section: Discussionsupporting
confidence: 93%
“…However, no report has been published on the effect of PTEN on maspin expression in bladder cancer. The results of the present study indicated that PTEN modulated the cell growth of bladder carcinoma cells in vitro and in vivo, which is consistent with the results of other studies [39,40]. The immunoblot assays revealed that PTEN downregulated Akt phosphorylation at both S473 and T308, whereas treatment with VO-OHpic trihydrate, which is a PTEN activity inhibitor, reversed the results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, its expression has been detected in cancer stem cells and has been implicated in their migration and invasion [57]. Paradoxically, trangelin has been described as both promoting and inhibiting bladder cancer [58,59]. The paradox is potentially resolved if timing and transient transgelin expression is important in the progression of bladder cancer as it is in the formation of a blastema.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is actively involved in the actin-cytoskeletal rearrangements regulating cell migration, podosome formation, tissue invasion, and matrix remodeling [52,53]. TAGL is associated with a specific sub-population of actin filament bundles, and its depletion increased the capacity of cells to form podosomes, increased the actin dynamics, and enhanced the tumorigenic properties of cells [54,55]. Most studies reported that TAGL acts as a tumor suppressor [56], inhibiting cell migration, suppressing the 92-kDa type IV collagenase (MMP-9) [57], and being down-regulated by the Ras pathway [58] as well as silenced through epigenetic mechanisms, which involve TAGL promoter hypermethylation [59,60].…”
Section: Discussionmentioning
confidence: 99%